THE IMPORTANCE OF LAND REGISTRATION TO SUPPORT SUCCESSFUL ENVIRONMENTAL MANAGEMENT - Mira Novana Ardani (Diponegoro Law Review, 2020)
Land registration provides legal certainty and protection to holders of land rights. In its implementation it does not always go well, so that what is the goal can not be achieved. A person or legal entity cannot prove that he is the legal owner of a parcel of land. This can lead to land conflicts. Land conflicts can cause overlapping land tenure and overlapping land permits which often results in environmental damage. This research uses a normative juridical approach. Normative juridical research is research focused on examining the application of rules or norms in positive law. The research objective is to find out what ways can be done so that through land registration activities can support the success of environmental management. The results of the study explained that land registration activities through systematic land registration acceleration resulted in land certification for plots of land that had met the requirements, and could strengthen the one map policy database, so that administrative order could be achieved. It also makes land use plans to support the achievement of national development goals and the greatest prosperity of the people,  so as to realize environmental sustainability.